2010
DOI: 10.1073/pnas.0907122107
|View full text |Cite
|
Sign up to set email alerts
|

Random cell movement promotes synchronization of the segmentation clock

Abstract: In vertebrate somitogenesis, the expression of segmentation clock genes oscillates and the oscillation is synchronized over nearby cells. Both experimental and theoretical studies have shown that the synchronization among cells is realized by intercellular interaction via Delta-Notch signaling. However, the following questions emerge: (i) During somitogenesis, dynamic rearrangement of relative cell positions is observed in the posterior presomitic mesoderm. Can a synchronized state be stably sustained under ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 37 publications
4
96
1
Order By: Relevance
“…This leads to the emergence of spin-waves in one dimension [29,30] and topological defects [31] in two dimensions. These facts, that relate synchronization theory and statistical mechanics, were often overlooked in studies of motile oscillators [32][33][34][35][36][37][38]. Here, we discuss how the motion of these topological excitations and the corresponding annihilation dynamics is affected by the motion of the oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the emergence of spin-waves in one dimension [29,30] and topological defects [31] in two dimensions. These facts, that relate synchronization theory and statistical mechanics, were often overlooked in studies of motile oscillators [32][33][34][35][36][37][38]. Here, we discuss how the motion of these topological excitations and the corresponding annihilation dynamics is affected by the motion of the oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…Bénazéraf et al [6] have recently quantified random cell motion in the mouse PSM while, in a theoretical study, Uriu et al [7] have demonstrated that random cell movement enhances synchronisation of neighbouring molecular oscillators. We now investigate the effects of random cell movement on the mitosis-perturbed phase dynamics introduced in Sect.…”
Section: Investigating the Perturbation To Oscillator Synchronisationmentioning
confidence: 99%
“…Random cell movement has also been quantified in zebrafish [1], although spatial variation in motility rates along the AP axis has not, to the best of our knowledge, been documented. A recent computational study has indicated that random cell movement should increase synchronisation in a population of locally coupled oscillators [7].…”
Section: Introductionmentioning
confidence: 99%
“…From experimental studies it is known that individual oscillating cells move so as to change their relative positions, and that synchronization is recovered upon perturbation that initially destroy synchrony. Uriu et al (2010) mathematically show that synchronization can be maintained under random cell movement, and that such movement actually reduced the timespan of reestablishing synchrony following perturbation.…”
Section: Synchronized Oscillations: the Vertebrate Segmentation Clockmentioning
confidence: 99%